Acute Pancreatitis Induced Fluid Collections - The Naming Game - Christopher, Dana M; Chaput, Kimberly J; Fairley, Kimberly J; Mowery, Andrew D; Valente, Christopher; Stewart, Blake A; Bonebrake, Steven R; Khara, Harshit; Johal, Amitpal S (JOP. Journal of the Pancreas, 2015)
No abstract available. Image: Geisinger Medical Center. Danville, PA, USA.